Hubungan Gaya Belajar Dengan Stres Akademik Pada Mahasiswa Program Studi Bimbingan Dan Konseling Universitas Sriwijaya - Salsabila Laurensia; Risma Anita Puriani (Educatio, 2025)
This study aims to explore the relationship between learning styles and academic stress among students of the Counseling Education Program at Sriwijaya University. Academic stress is often experienced by students due to high academic pressures, which can affect their learning performance. This research employs a quantitative approach with a descriptive design, involving students from the 2023 and 2024 cohorts. Data were collected using a Likert scale questionnaire. The results indicate that 70% of students who understand their learning styles experience a reduction in academic stress, while 60% of students with structured learning styles experience higher stress. There is a positive and significant relationship between learning styles and academic stress, where students applying appropriate learning styles tend to experience lower levels of stress. These findings suggest that awareness of individual learning styles can serve as a strategy for coping with academic stress. It is hoped that this research can contribute to the development of interventions aimed at reducing academic stress among students.